Kepastian Hukum Hak Pengelolaan Atas Tanah Badan Pengusahaan Batam terhadap Pendayagunaan Pulau Rempang - Anisa, Rada; Supriyo, Agus (Universitas Batanghari Jambi, 2024)
The Basic Agrarian Law is a legal reform in the agrarian sector. In the utilization of islands, especially the management of small islands, permission must be obtained. Management Rights are partially delegated to government agencies including Local Governments, State-Owned Enterprises, Regional-Owned Enterprises, PT.Persero, Authority Bodies and other legal entities to be used according to their respective duties. The existence of Land Management Rights (HPL) does not guarantee an island to be utilized by interested parties, including the utilization of Rempang Island which will be used as a National Strategic Project (PSN). The existence of regulations governing special provisions in the management of small islands must also be considered and examined so that some parties do not feel disadvantaged. This research will answer the questions of (1) How is the legal certainty of the Batam Concession Agency's Land Management Rights in the utilization of Rempang Island, (2) How is the Batam Concession Agency's problem in the management and utilization program of Remapang Island. This research uses normative juridical research by reviewing the applicable laws and regulations and using secondary data as the main data.